2023
DOI: 10.3390/polym15081951
|View full text |Cite
|
Sign up to set email alerts
|

Potential Additives in Natural Rubber-Modified Bitumen: A Review

Abstract: Conventional bitumen pavement is no longer suitable for handling increasing loads and weather variations, which cause road deterioration, Thus, the modification of bitumen has been suggested to counter this issue. This study provides a detailed assessment of various additives for modifying natural rubber-modified bitumen used in road construction. This work will focus on the use of additives with cup lump natural rubber (CLNR), which has recently started to gain attention among researchers, especially in rubbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 90 publications
0
6
0
Order By: Relevance
“…The presence of polymer in reclaimed asphalt improves the adhesion between the asphalt and the aggregate, making the asphalt mix more resistant to cracking, which increases the ITS ratio and moisture resistance [25,26]. The polymers improve the adhesion between the asphalt and the aggregate, making it more difficult for water to penetrate the mix and weakening the bond between the asphalt and the aggregate, making it less susceptible to moisture damage [27].…”
Section: Indirect Tensile Strength and Moisture Sensitivitymentioning
confidence: 99%
“…The presence of polymer in reclaimed asphalt improves the adhesion between the asphalt and the aggregate, making the asphalt mix more resistant to cracking, which increases the ITS ratio and moisture resistance [25,26]. The polymers improve the adhesion between the asphalt and the aggregate, making it more difficult for water to penetrate the mix and weakening the bond between the asphalt and the aggregate, making it less susceptible to moisture damage [27].…”
Section: Indirect Tensile Strength and Moisture Sensitivitymentioning
confidence: 99%
“…These distinctive qualities include elasticity, thermal stability, resilience, and the ability to tolerate high strain [2]. There are three primary different types of natural rubber which are natural rubber latex (NRL), epoxidized natural rubber (ENR) and a recently developed type called cup lump natural rubber (CLNR) [3], which is created when latex is left to coagulate in the presence of bacteria.…”
Section: Natural Rubber As a Bitumen Modifiermentioning
confidence: 99%
“…At present, whether from the perspective of waste disposal or simply to improve the performance of bitumen, many scholars have undertaken work on the modification of bitumen using waste rubber powder [9,10]. It was found that waste rubber powder has many advantages as an asphalt modifier, such as improving the durability, fatigue resistance, and economic benefits of asphalt pavement [11][12][13].…”
Section: Of 13mentioning
confidence: 99%